Randomization in studies with unequal allocation - Kuznetsova, Olga M. (Henry Stewart Talks, 2016)
Unequal allocation in clinical trials, Allocation ratio preserving procedures, Variations in unconditional allocation ratio, Permuted block design (PBR), Brick tunnel randomization (BTR), Wide brick tunnel randomization (WBTR), Biased coin randomization (BCR)